Financial Literacy as a Mediating Mechanism between Good Governance and Cooperative Financial Performance: Perception Evidence from Bekasi City, Indonesia - Panata Bangar Hasioan Sianipar; Christina Tri Setyorini; Yanuar Eko Restianto; Eliada Herwiyanti; Puji Lestari; Agung Praptapa (Greenation Research & Yayasan Global Resarch National, 2026)
Research on the relationship between good governance and financial performance in cooperatives still remains as interesting topic for study. This study aims to examine the relationship between good governance and financial performance in cooperatives through the perceptions of supervisors, board members, and cooperative members. Mediating and control variables were used to strengthen the research findings. Research data were collected by distributing questionnaires to respondents meeting the criteria of supervisors, board members, and active cooperative members registered in Bekasi City. The respondents' data were analysed using Smart PLS 3 to obtain results for the outer model and inner model. The study found that independence variable has a significant effect on literacy, and the literacy variable has a significant effect on performance. The results of the hypothesis testing showed that the relationship between the tested variables had an effect but was not significant. The conclusion drawn from this study is that, in addition to independence, it is necessary for board members to have sound financial knowledge to support the management of the cooperative. This study also contributes by recommending that cooperative board members acquire adequate financial knowledge.